Establishment of a Novel Simplified Surgical Model of Acute Liver Failure in the Cynomolgus Monkey - Cai, Lei (Biomed Res Int, 2016)
Models using large animals that are suitable for studying artificial liver support system (ALSS) are urgently needed. Presently available acute liver failure (ALF) models mainly involve pigs or dogs. Establishment of current surgical ALF models (hepatectomy/devascularization) requires either very good surgical skills or multistep processes—even multiple stages of surgery. Therefore, it is necessary to develop a simplified surgical method. Here we report a novel simplified surgical ALF model using cynomolgus monkeys. Six monkeys underwent portal-right renal venous shunt combined with common bile duct ligation and transection (PRRS + CBDLT). Postoperatively, the monkeys had progressively increased listlessness, loss of appetite, and obvious jaundice. Blood biochemistry levels (Amm, ALT, AST, TBiL, DBiL, ALP, LDH, CK, and Cr) and prothrombin time (PT) were significantly increased (all P < 0.01) and albumin (ALB) was markedly reduced (P < 0.01) compared with baseline values. Histological examination of liver specimens on postoperative day 10 revealed cholestasis and inflammation. PRRS + CBDLT produced ALF that closely correlated with clinical situations. Compared with other surgical or drug ALF models, ours was simplified and animals were hemodynamically stable. This model could provide a good platform for further research on ALSS, especially regarding their detoxification functions.